Sea Change: Using Citizen Science to Inform Fisheries Management. (10th March 2021) - Bonney, Rick; Byrd, Julia; Carmichael, John T; Cunningham, Leda; Oremland, Laura; Shirk, Jennifer; Von Harten, Amber
Abstract: Increasing costs are challenging the capacity for resource management agencies to keep up with mounting needs for robust data about fish populations and their habitats. Furthermore, trust among scientists, government agencies, and the public is fundamental to effective fisheries management, and relations among these three groups are increasingly strained when decisions about fishing limits are made (or are perceived to be made) on the basis of limited information or analysis. In the South Atlantic region of the United States, the South Atlantic Fishery Management Council has begun building a citizen science program to increase the quantity and quality of data used for fisheries management decisions throughout the region and to build trust and foster mutual understanding among those involved in the process. The goal is to build on existing management infrastructure to address key challenges to managing fisheries for long-term sustainability. In the present article, we examine the collaborative process used to establish the program.